Effects of Carbohydrate-Rich Diets Containing Snail Digestive Juice on the Growth Performance and Glycosidase Activities of Nile Tilapia (Oreochromis niloticus) - Melecony, Ble Celestin; Gopeyue, Yeo Maurice; Olivier, Etchian Assoi; Laurent, Yao Alla; Soumaila, Dabonne (Pakistan Journal of Nutrition, 2019)
Background and Objective: In fish feed, fishmeal is the main source of protein that provides energy for fish growth. However, its availability is limited due to the overexploitation of capture fisheries and its price continues to increase each year. The replacement of fishmeal with less expensive energy-rich feed ingredients is necessary for the sustainable development of aquaculture. The objective of this study was to evaluate the effects of different levels of the digestive juice of the snail Archachatina ventricosa in carbohydrate-rich diets on the growth performance and intestinal glycosidase activities of Nile tilapia (Oreochromis niloticus) Materials and Methods: Five experimental diets (R-0, R-1.5, R-2.5, R-5 and R-I) were formulated based on different levels of snail digestive juice (0, 15, 25 and 50 mg g–1). The diet R-I contained 5% inactivated digestive juice. O. niloticus fingerlings with an initial body weight of 22.55±2.29 g reared in glass hatchery tanks were fed with the experimental diets for 56 days. Results: The daily weight gain (DWG), specific growth rate (SGR), feed conversion rate (FCR), protein efficiency ratio (PER), intestinal glycosidase activities and fish body composition were significantly (p